Rapid discrimination of maggots utilising ATR-FTIR spectroscopy. (April 2015) - Pickering, Claire L.; Hands, James R.; Fullwood, Leanne M.; Smith, Judith A.; Baker, Matthew J.
Highlights: ATR-FTIR can provide a rapid, cheaper and objective technique to identify maggots. Enabling in situ detection and keeping operational tempo. High sensitivities and specificities of identification achievable. Proof of principle study shows promise to expand the forensic scientist's toolbox. Abstract: Entomological evidence is used in forensic investigations to indicate time since death. The species and age of maggots or flies that are present at the scene can be used when estimating how much time has passed since death. Current methods that are used to identify species and developmental stage of larvae and fly samples are highly subjective, costly and often time consuming processes and require the expertise of an entomologist or species identification via DNA analysis. The use of vibrational spectroscopy, as an alternative identification method, would allow for a quicker, cheaper and less subjective technique and would allow entomological evidence to be used more commonly in the forensic process. This proof of principle study shows the potential for using attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR) as a rapid tool for differentiating between various species of larvae, such as those commonly found at crime scenes. The proposed regime would provide a rapid and valuable tool resulting in reduced time for both species identification and life cycle determination, particularly in forensic situations.